(untitled) (Research, Society and Development, 2020)
Oral health is considered a fundamental element for health, general well-being and for the quality of life. The relationship between sport and oral health has been widely investigated through studies that focus mainly on the relationship between dental trauma and oral health. However, in addition to dental trauma, other oral health problems affect sportspeople. Athletes are a population particularly vulnerable to problems of the oral cavity, exacerbated by risk factors related to the demands of training and the body itself. Contrary to what one might think, there is an intimate relationship between an adequate oral condition and the performance of the athlete in the practice of the sport, and this performance can be compromised by the presence of the most varied oral problems. This article consists of a critical review of the literature on the influence that an athlete’s Oral Health can interfere with his physical performance, carried out through a selection of articles published in scientific journals indexed in specific databases (PubMed, Scielo, Science Direct and Google Scholar), aiming at presenting and synthesizing results of some primary studies. According to the results presented in this review, it is suggested that oral diseases can negatively impact sports performance either directly or indirectly and that well-treated oral health can contribute to physical development, improve systemic health, well-being, quality of life, and consequently better sports performance.